2001
DOI: 10.1080/104732201750169778
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Beryllium Number Concentration as a Possible Metric for Chronic Beryllium Disease Risk

Abstract: Beryllium is a lightweight metal which causes a chronic granulomatous lung disease among workers who become sensitized to it. Recent research has shown a persistence of the disease despite efforts at control with mean exposures below the Occupational Safety and Health Administration (OSHA) occupational exposure limit of 2 ¹ g/m 3 . Results of our current research con rm a previous nding in certain plants that particle number concentrations are higher in areas where historical estimate of risk showed a high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…To date, the high-risk processes in primary beryllium metal production have shown particle number concentrations in the submicron size range that are orders of magnitude higher than those found in lower-risk processes in the same facility (39). Distinguishing characteristics of machining aerosols in metal machining are limited (24).…”
Section: Physicochemical Determinants Of Riskmentioning
confidence: 99%
“…To date, the high-risk processes in primary beryllium metal production have shown particle number concentrations in the submicron size range that are orders of magnitude higher than those found in lower-risk processes in the same facility (39). Distinguishing characteristics of machining aerosols in metal machining are limited (24).…”
Section: Physicochemical Determinants Of Riskmentioning
confidence: 99%
“…For example, persons living near a beryllium plant also contracted the disease to a certain extent from environmental pollution at exposure levels several orders of magnitude lower than experienced by the workers. Particle number rather than particle mass may be more reflective of target organ dose [78]. The amount of beryllium to which a person has been exposed can be determined by measuring the urinary beryllium concentration [55,[79][80][81][82][83][84].…”
Section: R Klein Et Almentioning
confidence: 99%
“…Industrial hygiene studies demonstrated that disease prevalence correlates with beryllium ultrafine particle counts, not with beryllium mass measurements (Martyny et al 2000;McCawley et al 2001). Epidemiologic analyses showed that beryllium workers with the highest rates of disease are those involved in machining and grinding, tasks that generate significant amounts of dust (Kreiss et al 1996(Kreiss et al , 1997.…”
mentioning
confidence: 99%